A family of reconfigurable neurocomputers for the "intelligent factory" - Erdogan, S. S.; Abdul Rahman, Abdul Wahab (1992)
The neural network simulation plallorm provided by a family of Reconfigurable Machines (RM) suitable for massively parallel computations is presented in this paper. The RM family of neurocomputers range from a single board system capable (of providing supercomputer power to more elaborate systems suitable for very complex real time neural computation. The major architectural breakthrough in the design of RM neurocomputers is the fact that a completely reconfigurable platform, not only in the domain of communications and control but also in the domain of processing elements, is provided. Another contribution is the implementation of a last floating point sum of products circuit which uses special carry-save multipliers and extensive pipelining.